Dye-sensitized solar cell based on ZnO transparent conductive nanowire array electrode and preparation method thereof - CHEN JIANLIN; HU LINLIN; QIU WEI; CHEN JIAN; LI WEI; REN YANJIE; HE JIANJUN (2014)
The invention discloses a dye-sensitized solar cell based on a ZnO transparent conductive nanowire array electrode, and a preparation method of the dye-sensitized solar cell. The dye-sensitized solar cell mainly consists of the ZnO transparent conductive nanowire array electrode, a dye-sensitized TiO2 nano crystal semiconductor anode, an electrolyte and a counter electrode. The preparation method comprises the following steps: preparing the Al or In-doped ZnO transparent conductive nanowire array electrode through an electric sedimentation method and thermal treatment, subsequently preparing the dye-sensitized TiO2 nano crystal semiconductor anode in match with the ZnO nanowire array electrode in size, and finally assembling the cell. According to the dye-sensitized solar cell, a ZnO transparent conductive nanowire array of a suede structure is taken as a transparent electrode, the function of accelerating electron transport to a conductive electrode and the function of suede light trapping are achieved, and